SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI PREWEDDING BERBASIS WEB DI KOTA MEDAN MENGGUNAKAN METODE MOORA - Bin Tujuh, Raja; Aulia Rahmah, Sabrina; Satria, Andy (LPPM Universitas Putera Batam, 2024)
This research aims to develop a web-based decision support system (DSS) for selecting pre-wedding photoshoot locations in Medan, utilizing the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method. The DSS provides an efficient tool to assist couples in making informed decisions by evaluating various location options based on multiple criteria such as aesthetics, accessibility, and cost. The study employs a combination of data collection from popular pre-wedding locations, user preferences, and algorithmic processing to rank and recommend optimal locations. The MOORA method is chosen for its ability to handle multi-criteria decision-making problems effectively. The system's effectiveness was tested using real-world data, demonstrating its potential to simplify and enhance the decision-making process for users. Results indicate that the DSS can significantly reduce the time and effort required to choose a suitable pre-wedding location, while also providing personalized recommendations that align with user preferences. The findings suggest that the MOORA-based DSS can be a valuable tool for the wedding planning industry, offering a scalable solution that could be adapted to other location-based decision-making contexts.